Associations between neutering and idiopathic epilepsy in Labrador retrievers and Border collies under primary veterinary care in the UK. (October 2019) - Van Meervenne, S.; Volk, H.A.; Verhoeven, P.S.; Van Ham, L.; O'Neill, D.G.
Highlights: The majority of neutered epileptic dogs were neutered before the onset of seizures. Age at onset did not differ between intact and dogs neutered before onset. Cluster seizures did not differ across sex-neuter groups. Intact males had longer median survival times than dogs neutered before onset. Intact females had longer median survival times than dogs neutered before onset. Abstract: There are sparse published scientific data on associations between neutering and the severity and survival of dogs with idiopathic epilepsy. This study aimed to explore the timing of neutering with respect to onset of seizures in dogs with idiopathic epilepsy. Associations between neutering and both age of onset of seizures and the occurrence of cluster seizures or status epilepticus were examined. Survival analysis investigated the effects of sex-neuter categories. The median survival time of Border collies was compared with data previously reported in literature. The study included veterinary primary-care clinical data on 117 Labrador retrievers and 57 Border collies diagnosed with idiopathic epilepsy from the VetCompass project in the UK. The majority (74.2%; P  ≤ 0.001) of neutered cases were neutered before the onset of seizures. Age (years) at onset of seizures did not differ between dogs intact at time of onset and dogs neutered before onset of seizures (males 3.6 vs. 3.7; P  = 0.468 and females 3.4 vs. 4.1; P  = 0.154). Neuter status was not associated with the occurrence of cluster seizures (males P  = 0.947 and females P  = 0.844). Dogs intact at onset of seizures had longer median survival times than dogs neutered before onset of seizures (males, 1436 days vs. 1234 days; P  = 0.019; females, 1778.5 days vs. 1261 days; P  = 0.027). Median survival time of 1393 days for Border collies was longer than previously reported ( P  ≤ 0.001). These results do not support recommendations to neuter dogs with idiopathic epilepsy within an evidence-based treatment plan.